Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3174/ajnr.a6291
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Analysis of Natural Anastomoses between the Posterior and Anterior Cerebral Arteries in Moyamoya Disease and Syndrome

Abstract: BACKGROUND AND PURPOSE: Moyamoya disease is a chronic neurovascular steno-occlusive disease of the internal carotid artery and its main branches, associated with the development of compensatory vascular collaterals. Literature is lacking about the precise description of these compensatory vascular systems. Usually, the posterior circulation is less affected, and its vascular flow could compensate the hypoperfusion of the ICA territories. The aim of this study was to describe these natural connections between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…Second, the authors found a significant risk factor related to the cerebral infarction after surgery -the Suzuki stages of the nonoperative side. Indeed, as reported by Bonasia et al [5], in order to compensate the perfusion of ischemic areas, there exists a wide vascular anastomosis in the brain of MMD patients. Thus, operation on the more systematically unstable side may more induce a loss of moyamoya vessels, which may eventually affect cerebral blood flow in the opposite hemisphere.…”
Section: Dear Editormentioning
confidence: 93%
“…Second, the authors found a significant risk factor related to the cerebral infarction after surgery -the Suzuki stages of the nonoperative side. Indeed, as reported by Bonasia et al [5], in order to compensate the perfusion of ischemic areas, there exists a wide vascular anastomosis in the brain of MMD patients. Thus, operation on the more systematically unstable side may more induce a loss of moyamoya vessels, which may eventually affect cerebral blood flow in the opposite hemisphere.…”
Section: Dear Editormentioning
confidence: 93%
“…2 However, the anastomosis of PCA and ACA/ MCA will also increase the hemodynamic burden of posterior circulation and increase the risk of hemorrhage. 3 This should be noted during the clinical management of pediatric MMD patients. Meanwhile, other compensatory collaterals, such as extracranial arterial collateral circulation anastomoses from the facial, maxillary and middle meningeal arteries to the ophthalmic artery, and dural arteriolar anastomoses from the middle meningeal artery and occipital artery through the mastoid foramen and parietal foramen, may also have correlation with postoperative outcomes.…”
Section: The Significance Of Leptomeningeal Collaterals In Moyamoya Diseasementioning
confidence: 99%
“…DSA can not only evaluate the severity of stenosis in the terminal part of the internal carotid artery, but can also assess the degree of compensation from the external carotid artery and posterior circulation [ 98 , 99 ]. Bonasia et al [ 100 ] described the compensatory vascular systems in MMD and found 3 different types of anastomoses with different compensatory abilities, resulting from various perfusion needs of the anterior circulation. Recent studies based on DSA have mainly focused on the prediction of clinical outcomes and prognosis in MMD [ 101 - 103 ].…”
Section: Neuroimaging Evaluationsmentioning
confidence: 99%